Development of conceptual framework on the occupational stress for the construction projects management staff of China contractors / Yang Zi Fan - Yang, Zi Fan (2022)
Construction project management is one of the most stressful occupations. As China contractors thrived in Malaysia over a decade, their construction project management staff may suffer from occupational stress. This study aims to identify the types of stress, and the key causes of the occupational stress on construction projects management staff of China contractors through the questionnaire survey for 95 project management staffs. The research results show almost all staff suffered from occupational stress and half of them under considerable stress. The dominant types of occupational stress are feeling of tension and restlessness. Regarding the key causes of occupational stress, among 45 most popular key causes of occupational stress, the most significant key causes are project overload, lack of autonomy, poor communication, multitasking and lack of human. In the end of the research, some recommendations to release the occupational stress of the employees were raised.